Frog and toad are friends - Lobel, Arnold (An I can read book, 1970)
One summer day Toad was unhappy. He had lost the white, four-holed, big, round, thick button from his jacket. Who helped him look for it? His best friend, Frog. Another day, Frog was unhappy. He was sick in bed and looking green. Who gave him some tea and told him a story? His best friend, Toad. Whether they are telling stories, taking walks, or writing letters, Frog and Toad always help each other out, as best friends should. Here are five irresistible stories about their adventures together.